PKM KARANG TARUNA TUNAS KARYA KUNCIRAN INDAH - Gilang Ryan Fernandes; Redo Abeputra Sihombing (COVIT (Community Service of Health), 2021)
This community service was carried out at Karang Taruna Tunas Karya Kunciran Indah, with the title "PKM Karang Taruna Tunas Karya Kunciran Indah". Based on the results of interviews and observations conducted by the team proposing community service at Karang Taruna Tunas Karya Kunciran Indah, various problems were found in the Karang Taruna Tunas Karya Kunciran Indah, namely requiring a storage media file for data files and reports on all youth activities. easily accessible and secure. Given this problem, the purpose of implementing this community service program is to help make it easier for administrators to archive youth files using Google Drive and manage youth youth cash finances using a cash income and disbursement application that can be installed on each administrator's smartphone and cadet members. This activity uses a learning approach method in which there are presentations, application simulations, and hands-on practice for participants assisted by the team. So that participants can understand and study the material presented properly and can be useful and increase knowledge about storing and managing data for Karang Taruna Tunas Karya Kunciran Indah. Keywords: Google Drive, Apps, Cash In and Out, Android, Finance